Hubungan Hubungan Antara Faktor Internal dan Eksternal dengan Efikasi Diri PEserta Didik Sd dalam Pengembangan P5 - Dinda Septiandini; M Luthfi Oktarianto (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2026)
This study aims to examine the simultaneous relationship between internal and external factors and the self-efficacy of elementary school students in developing the Pancasila Student Profile Strengthening Project (P5). This study uses a correlational research design with a quantitative approach. The research subjects consisted of 125 fourth-grade students from five public elementary schools in Malang City, selected using cluster random sampling. Data collection techniques were conducted through interviews and the completion of validated questionnaires. Data analysis was performed using prerequisite tests and hypothesis testing through multiple linear regression analysis with the help of IBM SPSS for Windows software. The research findings show that internal and external factors together have a significant relationship with student self-efficacy, as indicated by a significance value (<0.001) < 0.05. The Adjusted R Square value of 0.257 indicates that the simultaneous contribution of internal and external factors to self-efficacy is 25.7%. These results confirm that the synergy between individual readiness and environmental support is very important in building students' confidence to complete the P5 project optimally.